Off the rim basketball and other religions in a Carolina childhood - Hobson, Fred C., 1943-; ebrary, Inc. (Columbia : University of Missouri Press, 2006)
"Hobson, a passionate follower of North Carolina basketball who once played briefly for the Tar Heels, tells the story of an eternal childhood relived each season. More than a basketball memoir, his account also depicts a seldom-viewed South through glimpses of a boyhood in the Carolina hills"--Provided by publisher.
Electronic reproduction.
Keywords: Hobson, Fred C., -- 1943-; University of North Carolina at Chapel Hill -- Basketball; North Carolina Tar Heels (Basketball team); Yadkin County (N.C.); Electronic books